РАЗВИТИЕ БРЕНДА КАК ФАКТОР ПОВЫШЕНИЯ КОНКУРЕНТОСПОСОБНОСТИ ТОВАРОВ НА РЫНКЕ - Ниязметова Ёкутхон Ботир (International Journal of Innovative Technologies in Economy, 2019)
The basic theoretical aspects and various approaches of the concepts of product competitiveness and branding are considered, the relationship between the concepts is shown, a full explanation of the important role of branding in improving product competitiveness is given.